Bosonic Dp-branes at finite temperature in TFD approach - Abdalla, MCB; Gadelha, A. L.; Vancea, IV (Elsevier B.V., 2004)
A general formulation of Thermo Field Dynamics using transformation generators that form the SU(1, 1) group, is presented and applied to the closed bosonic string and for bosonic D-p-brane with an external field.